Influence of different cosmetic vehicles in mechanical and physical properties of hair treated with oxidative hair dyes - Elaine Cabral Serrão; Robson Miranda da Gama; Michelli Ferrera Dario; Simone Aparecida da França-Stefoni; Valcinir Bedin; André Rolim Baby; Maria Valéria Robles Velasco (Universidade de São Paulo, 2018)
ABSTRACT Hair care products play a significant role in the cosmetic market and aim at improving hair brightness, breakage resistance, and color change. In this study, we analyzed the possibility of the formulation of oxidative dyes in different vehicles impacting the hair's both mechanical and physical properties. Light brown and light blond dyes were prepared using eight different vehicles. Among these, four vehicles were emulsifying agents and four gelling agents. Each formulation was applied to two types of virgin Caucasian hair (light blond and dark brown). Physical, chemical, and organoleptic properties of each formulation were assessed, as well as changes in hair parameters after oxidative dyeing, such as staining intensity, brightness, and breaking strength. The parameters of color and brightness differed in some formulations, but the hair type also responded differently. Brightness parameter was increased in dark brown hair colored with both dyes, whereas light blond hair showed the opposite result. Regarding the breaking strength, there were no significant differences between the two kinds of tresses. Cosmetic formulations should adjust the consumer desired effects (e.g. color change) in order to present minimal drawbacks (e.g. decrease of hair brightness and strength). Thus, the study of different vehicles is important when establishing the best oxidative dye formulation.